2001
DOI: 10.1038/sj.ijo.0801472
|View full text |Cite
|
Sign up to set email alerts
|

Reduced food intake in response to CGP 71683A may be due to mechanisms other than NPY Y5 receptor blockade

Abstract: INTRODUCTION:The purpose of this study was to test the continuing validity of the hypothesis that neuropeptide Y (NPY) produced in the brain controls food intake through an interaction with the NPY Y 5 receptor subtype.METHODS: The hypothesis was tested using CGP 71683A a potent and highly selective non-peptide antagonist of the NPY Y 5 receptor which was administered into the right lateral ventricle of obese Zucker faafa rats. RESULTS: Intraventricular injection of 3.4 nmolakg NPY increased food intake during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…To investigate its cross-reactivity, CGP 71683A has recently been studied in a series of both NPY and non-NPY receptor binding assays (Table 5). 135 Surprisingly, CGP 71683A was found to have equally high affinity for the serotonin reuptake recognition site and for cholinergic muscarinic receptors in the rat brain as for the NPY Y 5 receptor. Reasonably high affinity for a 2 -adrenergic receptors was also observed -a finding in Appetite suppression S Chamorro et al agreement with the original published studies on this compound.…”
Section: Npy Receptor Subtypesmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate its cross-reactivity, CGP 71683A has recently been studied in a series of both NPY and non-NPY receptor binding assays (Table 5). 135 Surprisingly, CGP 71683A was found to have equally high affinity for the serotonin reuptake recognition site and for cholinergic muscarinic receptors in the rat brain as for the NPY Y 5 receptor. Reasonably high affinity for a 2 -adrenergic receptors was also observed -a finding in Appetite suppression S Chamorro et al agreement with the original published studies on this compound.…”
Section: Npy Receptor Subtypesmentioning
confidence: 99%
“…135 Inflammatory mediators have been shown to negatively affect food intake and could be a further explanation for the decreased appetite observed with this compound. 140 In accordance with the above studies, CGP 71683A has recently been shown to reduce food intake equally in both wild type and in NPY-knockout mice.…”
Section: Npy Receptor Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…193,194 Mixed ligands of neuropeptide Y 5 receptors and 5-HT transporters have also been described. 195 The real future of neuromodulatory peptidergic mechanisms may well lie in the multitarget universe, and it is hard to comprehend the persistent obsession with selective agents only. To reiterate, disappointing results with a selective agent do not necessarily imply therapeutic irrelevance but, rather, invite exploitation by means of a multitarget strategy.…”
Section: Figmentioning
confidence: 99%
“…However, other authors reported no effects with their Y5-receptor blockers, 65 or suggested that the compound used in earlier studies 64 may have nonspecific effects. 66 Recent reports appear to again provide evidence for an important role of Y1 receptors in the regulation of feeding. 67 It is therefore still unclear which receptor subtype is the most promising target for therapeutically active NPY antagonists.…”
Section: Leptin Pathwaymentioning
confidence: 99%